Isolation of Pseudmonas flurecences and Aeromonas hydrophila from Siganus rivulatus and Siganus luridus in the water coastal of Latakia - تيماء نصور,; معينة بدران ,; عيسى كبيبو, (Latakia University Journal -Biological Sciences Series, 2023)
This research was conducted to isolate Pseudmonas flurecences and Aeromonas hydrophila bacteria from some Siganus fishes. Where 20 fish samples were collected from marine waters at the Assaid and Annozha port site (which is considered a polluted area) during the summer and winter seasons of 2022/2023. Some morphometric and biological measurements (height, weight, and sex) were carried out, in addition to a microbiological study of intestines, gills, and liver The results showed that the isolates of Pseudmonas flurecences were round in shape, shiny, medium to large in size, with a smooth edge, ranging in color from pale white to yellow, while the Aeromonas hydrophila isolates were round in shape, medium and small, with a domed edge, and their color ranged from pale white to yellow The results also showed increased mucus secretion, bleeding and congestion in the gills and skin, in addition to ascites in the abdominal area.